2021
DOI: 10.1111/eva.13242
|View full text |Cite
|
Sign up to set email alerts
|

Selection on fish personality differs between a no‐take marine reserve and fished areas

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…While rebuilding of local lobster populations was the main goal when implementing the MPAs, the decreased harvest pressure in these areas also conferred effects on several fish species. Striving to test hypotheses of general interest to conservation science, we deem the study of lobster and sympatric fish species as case studies with attributes that are transferable to other aquatic species using the marine environment for all or part of their life cycle (e.g., Sørdalen et al, 2018Sørdalen et al, , 2020Thorbjørnsen et al, 2021). Two wrasse species, goldsinny (Ctenolabrus rupestris) and corkwing wrasse (Symphodus melops), both harvested to provide cleaner fish services in the salmonid aquaculture industry, showed moderate positive responses to protection in MPAs reviewed herein.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While rebuilding of local lobster populations was the main goal when implementing the MPAs, the decreased harvest pressure in these areas also conferred effects on several fish species. Striving to test hypotheses of general interest to conservation science, we deem the study of lobster and sympatric fish species as case studies with attributes that are transferable to other aquatic species using the marine environment for all or part of their life cycle (e.g., Sørdalen et al, 2018Sørdalen et al, , 2020Thorbjørnsen et al, 2021). Two wrasse species, goldsinny (Ctenolabrus rupestris) and corkwing wrasse (Symphodus melops), both harvested to provide cleaner fish services in the salmonid aquaculture industry, showed moderate positive responses to protection in MPAs reviewed herein.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Tvedestrand fjord MPAs, Villegas-Ríos et al (2017b) suggested that a small no-take zone could be maladaptive for fjord cod by favoring behavioral phenotypes characterized by small home ranges. While testing this hypothesis for sea trout in the Tvedestrand fjord, Thorbjørnsen et al (2021) suggested a seascape mosaic of marine reserves, partially protected areas and areas open to harvest as a management tool to preserve behavioral variation in a sea trout population. Preserving behavioral variation is important to maintain a population's resilience to environmental change (Dingemanse et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations